The Importance of Digital Literacy in Facing the Impact of Information Technology on Student Character - Manan, Abdul; Kodrat, Hikmat; Rustandi, Apriya Maharani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The development of information and communication technology (ICT) has brought significant changes to the world of education and has influenced the character development of students. The use of digital technology provides opportunities to improve the quality of learning, but also raises various problems, such as declining ethics, low social empathy, plagiarism, and misuse of digital media. This shows that the ability to use technology technically is not necessarily accompanied by wise and characterful attitudes. Therefore, digital literacy is a crucial aspect in addressing the impact of technological developments on students' character. This study aims to examine the role of digital literacy in shaping and strengthening students' character in the digital era. The method used is a Systematic Literature Review (SLR) by examining relevant scientific articles, books, and policy documents published in the period 2015–2025. Data were obtained from Google Scholar, Scopus, and ResearchGate, then analyzed qualitatively through thematic selection and synthesis. The results of the study indicate that digital literacy encompasses cognitive, social, and ethical aspects that play an important role in the development of students' character, such as honesty, responsibility, independence, and digital ethics. Furthermore, information technology has both positive and negative impacts on student character, which is heavily influenced by digital literacy levels and the role of educators and educational institutions. This study recommends integrating digital literacy into the curriculum and strengthening the role of educators so that the use of technology in education focuses not only on technological mastery but also on character development in students.